SIRT3 in Cardiac Physiology and Disease - Koentges, Christoph; Bode, Christoph; Bugger, Heiko (Frontiers in Cardiovascular Medicine, 2016)
Functional defects in mitochondrial biology causally contribute to various human diseases, including cardiovascular disease. Impairment in oxidative phosphorylation, mitochondrial oxidative stress, and increased opening of the mitochondrial permeability transition pore add to the underlying mechanisms of heart failure or myocardial ischemia–reperfusion (IR) injury. Recent evidence demonstrated that the mitochondrial NAD+-dependent deacetylase sirtuin 3 (SIRT3) may regulate these mitochondrial functions by reversible protein lysine deacetylation. Loss of function studies demonstrated a role of impaired SIRT3 activity in the pathogenesis of myocardial IR injury as well as in the development of cardiac hypertrophy and the transition into heart failure. Gain of function studies and treatment approaches increasing mitochondrial NAD+ availability that ameliorate these cardiac pathologies have led to the proposal that activation of SIRT3 may represent a promising therapeutic strategy to improve mitochondrial derangements in various cardiac pathologies. In the current review, we will present and discuss the available literature on the role of SIRT3 in cardiac physiology and disease.